NILAI TROPONIN T (cTnT) PENDERITA SINDROM KORONER AKUT (SKA) - R A Nawawi; B Rusli; Fitriani Fitriani; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2006)
Acute Coronary Syndrome (ACS) is an emergency cardiac condition manifested by chest pain or other symptoms as the result ofischemic myocardium. Myocardial damage can be detected by Creatine Kinase MB (CK-MB), Lactate Dehydrogenase (LDH) and cTnTtests. CTnT can be used as criteria of therapy determination. The combination of CK-MB and cTnT are the most effective tests if theearly myocardium damage is unknown, to evaluate cTnT, CK-MB, and LDH values in patients with Acute Coronary Syndrome (ACS) atWahidin Sudirohusodo Hospital, Makassar. Secondary data were collected from the medical records (from March to July 2005 period)at Wahidin Sudirohusodo Hospital, Makassar. Chi-square and Spearman correlation were carried out to analyze the collected data. Theinvestigators found 90 patients with ACS consisted of 57 males (63.33%) and 33 females (36.67%). The highest cTnT Value of 0.1 to2.0 ng/ml was found in 39 patients (43.33%), 30 females (52.63%). Significant correlation showed by Chi-square test between IMAEKG and cTnT values (p < 0.05). Spearman correlation test demonstrated significant correlation between cTnT value and CK-MB andLDH (p = 0.001). Most cTnT values were found in the male patients with ACS, aged 60 to 69 years and significantly correlated withIMA’s ECG, CK-MB and LDH.